2016
DOI: 10.1111/tesg.12205
|View full text |Cite
|
Sign up to set email alerts
|

Size of Town, Level of Education and Life Satisfaction in Western Europe

Abstract: I analyse the effect of living in settlements of different sizes on individual life satisfaction. The literature usually finds a negative correlation between life satisfaction and size of town. Here I cluster the population by level of education; the results show that people get dissatisfaction from living in large centres and that both education and income attenuate this effect. In particular, high education renders the cities and their features more enjoyable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 73 publications
2
3
0
Order By: Relevance
“…Support for this hypothesis is found in empirical research, where Morrison and Weckroth (2018) reported that urban agglomeration raises the income and wellbeing returns for those with tertiary education. Similar evidence is provided by Burger et al (2020), who found that highereducated individuals with higher incomes are happier in cities in the Western part of Europe and North America, a finding also reported in the study by Migheli (2017) using the World Values Survey for Western Europe. Likewise, Carlsen and Leknes (2019) found for Norway that young, single people without children, as well as highereducated people generally, report higher levels of SWB in more populous cities.…”
Section: Between-group Heterogeneitysupporting
confidence: 87%
“…Support for this hypothesis is found in empirical research, where Morrison and Weckroth (2018) reported that urban agglomeration raises the income and wellbeing returns for those with tertiary education. Similar evidence is provided by Burger et al (2020), who found that highereducated individuals with higher incomes are happier in cities in the Western part of Europe and North America, a finding also reported in the study by Migheli (2017) using the World Values Survey for Western Europe. Likewise, Carlsen and Leknes (2019) found for Norway that young, single people without children, as well as highereducated people generally, report higher levels of SWB in more populous cities.…”
Section: Between-group Heterogeneitysupporting
confidence: 87%
“…In the U.S., like in some other countries, an urban-rural happiness gradient has been observed that rises from lowest levels in large cities to highest levels in the rural periphery (Berry, Okulicz-Kozaryn 2011; Winters 2017) Similarly, Requena (2016) found higher subjective well-being in rural areas 194/354 compared to cities, albeit just in economically more developed countries, while in less developed countries, the rural environment cannot compete with urban resources for creating subjective well-being. Migheli (2017) confirmed the negative effect of urbanisation levels on life satisfaction also in European countries. He argues however, that the effect is less pronounced for welleducated who benefit more from the urban environment.…”
Section: Approaches To Investigate Rural Quality Of Life and Aspects supporting
confidence: 65%
“…This is achieved using five dummies clustering towns according to the number of inhabitants; cities with more than 100,000 residents are used as a reference category. In Italy, centres of this size are either large provincial chief towns or regional capitals, and therefore, are characterised by the presence of numerous commercial services ( Migheli, 2017 ). Finally, some regressions control for the variation in the number of weekly purchases of food in different types of stores, such as supermarkets, local shops, and stores located far from the neighbourhood where the household lives, local market, and producers (for fresh food).…”
Section: Methodsmentioning
confidence: 99%